Psychological aspects of modern educational information technology high school - Dovbysh, M. A.; Voloshin, N. A.; Syrtsov, V. K. (Zaporozhye Medical Journal, 2013)
Psychological aspects were studied on 240 students of 4th year study of medical faculty by filling in a form and interrogatory while practical classes with following processing. It was found that students entering the high school have different pre-study preparation level and individual features of cognitive processes. Creation and application of innovative education technologies in this connection have to be guided on improvement of effectiveness of comprehension perception and master the students of study material contents on a base of due regard for their individual and typological peculiarities of cognition activity. In our days it have to make scientific-psychological grounds of professional forming stages and personal specialist’s competence and also work-out and inculcation of psychological innovative education technologies accompany.